Translation elongation defects activate the Caenorhabditis elegans ZIP-2 bZIP transcription factor–mediated toxin defense - Marina Kniazeva; Gary Ruvkun (Proceedings of the National Academy of Sciences, 2025)
The Caenorhabditis elegans bZIP transcription factor ZIP-2 is activated by toxins or mutations that inhibit translational elongation. The zip-2 DNA-binding protein is encoded in a downstream main open reading frame (mORF), but under normal translation elongation conditions only an upstream overlapping oORF -1 frameshifted from mORF is translated. Mutations or toxins that slow translational elongation, but not inhibitors of translational initiation or termination, activate ZIP-2. An mORF initiation codon mutation does not disrupt the normal zip-2 response to translational elongation defects, suggesting that zip-2 activation does not depend on this ATG. An mORF early termination mutant can be activated by strong translation elongation inhibition, suggesting that translation initiated upstream on oORF +1 frameshifts when elongation is inhibited to the mORF reading frame downstream of the stop codon to activate a fused oORF/mORF ZIP-2 transcription factor. The protein and DNA sequences of zip-2 oORF and mORF are conserved across the Caenorhabditis , suggesting selection for particular codons sensitive to translational elongation defects. Mutations that disrupt the oORF initiation codon constitutively activate zip-2 , but not if the mORF initiation codon is also mutant, showing that zip-2 oORF competes with mORF for translational initiation. oORF initiation codon mutation-activated zip-2 slows C. elegans growth, and this slow growth is suppressed by a zip-2 null mutation. A zip-2 null mutant also strongly suppresses the growth arrest caused by translational elongation inhibitors. Thus, ZIP-2 is both a sensor of translational elongation attack, and a defense regulatory output via its activation of response genes.